The elusive costs of sovereign defaults - Eduardo Levy-Yeyati; Ugo Panizza (Inter-American Development Bank, Research Department, 2006)
Few would dispute that sovereign defaults entail significant economic costs, including, most notably, important output losses. However, most of the evidence supporting this conventional wisdom, based on annual observations, suffers from serious measurement and identification problems. To address these drawbacks, we examine the impact of default on growth by looking at quarterly data for emerging economies. We find that, contrary to what is typically assumed, output contractions precede defaults. Moreover, we find that the trough of the contraction coincides with the quarter of default, and that output starts to grow thereafter, indicating that default episode seems to mark the beginning of the economic recovery rather than a further decline. This suggests that, whatever negative effects a default may have on output, those effects result from anticipation of a default rather than the default itself.
Keywords: 330; Staatsbankrott; Öffentliche Schulden; Soziale Kosten; Makroökonomischer Einfluss; Wirtschaftswachstum; Schätzung; Schwellenländer